The Influence of Think Talk Write Learning Model on Students' Writing Skills - Saputra, Yuyus; Syakira, Sitti; Kastury, Hilda Sri (JALL (Journal of Applied Linguistics and Literacy), 2024)
This study aims to determine the influence of the Think Talk Write learning model on the ability to write announcement texts among eighth grade students at SMPN 18 Tasikmalaya in the 2023/2024 academic year. This research employed a quasi-experimental method with a quantitative approach. The research sample consisted of 40 eighth-grade students, with 20 students from class VIII-D serving as the experimental group and 20 students from class VIII-A serving as the control group. Data collection was carried out using pretests and posttests. The pretest was administered to both groups before the treatment. After the treatment, a posttest was conducted for both groups. To analyze the data, the researcher used an independent sample t-test with SPSS. The average pretest score in the experimental class using the Think Talk Write learning model was 56.35, and the average posttest score was 80.70. The average pretest score in the control class using the conventional learning model was 51.65, and the posttest score was 71.40. Thus, the learning outcomes in the experimental class were more successful than those in the control class. Based on statistical testing (t-test), the difference in the average posttest scores between the experimental and control classes showed that the Sig. (2-tailed) value was less than 0.05, specifically 0.013 < 0.05. This indicates that the Think Talk Write model has a significant effect on the ability to write announcement texts among eighth-grade students at SMPN 18 Tasikmalaya in the 2023/2024 academic year.